2017
DOI: 10.1534/genetics.117.300106
|View full text |Cite
|
Sign up to set email alerts
|

Lipid and Carbohydrate Metabolism in Caenorhabditis elegans

Abstract: Lipid and carbohydrate metabolism are highly conserved processes that affect nearly all aspects of organismal biology. Caenorhabditis elegans eat bacteria, which consist of lipids, carbohydrates, and proteins that are broken down during digestion into fatty acids, simple sugars, and amino acid precursors. With these nutrients, C. elegans synthesizes a wide range of metabolites that are required for development and behavior. In this review, we outline lipid and carbohydrate structures as well as biosynthesis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(62 citation statements)
references
References 345 publications
0
62
0
Order By: Relevance
“…Our LC-MS results indicated that cyclopropane FA levels are undetectable in DA bacteria (Figure 1G). Since C. elegans are unable to synthesize cyclopropane FAs and rely on dietary sources for these compounds 62,63 , DA-fed worms have a lower abundance of cyclopropane FAs, in addition to reduced levels of most PUFAs, compared to OP-fed worms (Figure 1F). We therefore speculate that the decreased targeting of SEIP-1 to peri-LD cages in DA-fed worms may be partly explained by the lower levels of cyclopropane FAs and PUFAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our LC-MS results indicated that cyclopropane FA levels are undetectable in DA bacteria (Figure 1G). Since C. elegans are unable to synthesize cyclopropane FAs and rely on dietary sources for these compounds 62,63 , DA-fed worms have a lower abundance of cyclopropane FAs, in addition to reduced levels of most PUFAs, compared to OP-fed worms (Figure 1F). We therefore speculate that the decreased targeting of SEIP-1 to peri-LD cages in DA-fed worms may be partly explained by the lower levels of cyclopropane FAs and PUFAs.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore speculate that the decreased targeting of SEIP-1 to peri-LD cages in DA-fed worms may be partly explained by the lower levels of cyclopropane FAs and PUFAs. Further, C. elegans use cyclopropane FAs for a substantial portion of the TAGs they produce 63 . It is therefore possible that lower levels of cyclopropane FAs in DA-fed worms may also impede TAG synthesis, resulting in overall reduced lipid content (Figure 1A, B).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in transition zone components like NPHP4 cause human ciliopathies 35 , suggesting that EV defects may contribute to ciliopathies such as nephronophthisis and polycystic kidney disease 4 . TTM-5 is a dihydroceramide desaturase (DEGS1/2) ortholog, which acts in a ceramide biosynthesis pathway to convert dihydroceramide to ceramide 22 . Ceramide is a bioactive signaling lipid that plays roles in ciliogenesis, ciliary TGF-β receptor/sonic hedgehog signaling, and exosome biogenesis 2,19 .…”
Section: Dihydroceramide Desaturase Ttm-5 Is Required For the Extende...mentioning
confidence: 99%
“…β-branched fatty acids are highly unusual because they cannot be obtained via canonical fatty acid biosynthesis from acetate or propionate, nor from leucine-derived monomethyl branched chain fatty acids which contain a methyl branch at the terminal carbon (Fig. 4A) 39,56,57 . We therefore hypothesized that the unusual β-methyl group is installed by an S-adenosyl methionine (SAM)-dependent methyltransferase.…”
Section: A Methyltransferase Conserved Across Nematodamentioning
confidence: 99%